Directing The Documentary - Rabiger, Michael (New York Focal Press Taylor & Francis Group, 2015)
Directing the Documentary, Sixth Edition is the definitive book on the form, offering time-tested principles to help you master the craft. Ideal for documentary courses as well as aspiring and established documentary filmmakers, this book has it all, with in-depth lessons and insider perspectives on every aspect of preproduction, production, and postproduction. Focusing on the hands-on work needed to make your concept a reality, this new edition covers it all, from the fundamental to advanced elements of directing and more. It includes dozens of projects, practical exercises, and thought-provoking questions, and provides best practices for researching and honing your documentary idea, developing a crew, guiding your team, maintaining control throughout the shoot, and much more. This new edition features: A two-stage cinematic learning process: camera observation skills, then advanced storytelling Dozens of real-world exercises and case studies to demystify production processes and enhance your skills Easy-to-comprehend guidance in the creative, technical, and artistic aspects of directing Fresh coverage of the latest filmmaking technology Expanded sections on grant writing and fundraising, emphasizing proposal and pitching skills A self-assessment of your interviewing skills and expanded coverage of narration-writing A companion website (www.directingthedocumentary.com) that includes handy production checklists and forms, updated projects, exercises, and video examples In Directing the Documentary, Sixth Edition Michael Rabiger combines expert advice on the storytelling process and technical aspects of documentary filmmaking with sound commentary on the philosophical underpinnings of the art, providing the practical and holistic understanding you need to become a highly-regarded, original, and ethical contributor to the genre.
Part 1: You and Your Ideas 1 You and Film Authorship The Director’s Temperament Unfinished Business: How Your Life Has Usefully Marked You Project 1-1: The Self-Inventory (Marks and Themes) Project 1-2: What Is the Family Drama? The Work of the Director Witnessing with the Future Box Ethnography Working for Social Change A Rewarding Way of Life Learning from What you Shoot Filmmaking Democratized The Ordinary Can be Extraordinary Documentaries that Cross Boundaries and Buck Trends Importance of Creativity Documentary as a Prelude to Directing Fiction Getting an Education Film School Teaching Yourself Planning Your Future Journals Internships as a Student Hands-On Learning 2 The Nature of Documentary Beginnings Grierson’s Definition Documentary as Art An Oral Tale with a Purpose Art Finds Order Characters with Goals Philosophies of Approach Observational Mode Participatory Mode Making Incursions Giving, Not Just Taking A Workhorse Genre Testing for Documentary Values Learning From Your Work The Artistic Process When You Lose Your Way Privacy and Competition Issues Hostile Environments Hands-On Learning Part 2: Documentaries and Film Language 3 Documentary History Technology and Screen Language Birth of the Cinema The Documentary Arrives on the Scene Documentary Paradoxes The Cinematic Eye Sound Travelogue Essay Films Shooting Goes Mobile Direct Cinema and Cinéma Vérité Observational Documentary Participatory Documentary Waiting for Privileged Moments Objectivity and Subjectivity Which Approach is Best? The Ascendency of Editing The Three-Act Structure in Documentary Video and Digital Technology Eclectic Filmmaking Longitudinal Study Brechtian Protest Documentary Noir Diary Ambush and Advocacy Archive-Based Filmmaking 3D Documentaries The Interactive Documentary Hands-On Learning 4 Constructing Reality The “Contract” and Exposition Actuality and Evidence Types of Actuality Objectivity, Balanced Reporting, and Propaganda Fairness Evidence Then and Now Documentary is Not Reality, But a Construct Drama Authored Constructs Conflict Character-Driven or Plot-Driven Stories Dramatic Tension Development Film Language Form and Style Hands-On Learning 5 Story Elements and Film Grammar Perception and Making Stories How Screen Language Mimics Consciousness Documentary Ingredients and Human Consciousness Elements A Guiding Theory Shots are Like the Human Gaze Cuts Camera Movement Motivated Camera Movements and Cuts Denotation and Connotation The Camera in Relation to Action Preparing to Shoot with Feeling The Actor and the Acted-Upon Observing a Conversation Hunting Subtexts Hidden Agendas and Subtexts Attention and Focus Eye Contact and Eyelines Looking At, and Looking Through Scene Geography and Axes Scene Axis Camera Axis Panning and Cutting Screen Direction Changing Screen Direction Shot Duration, Rhythm, and Demand on the Audience Generating Options Shot Duration Visual Rhythm Rhythms Help Us Concentrate Speech Rhythms Sequences as Building Blocks Elision Transitions and Transitional Devices Picture Transitions Sound Transitions Overlap Cuts Your Dual Roles: Observer and Storyteller Conflicts Between the Two Resolving Tensions Hands-On Learning Part 3: Preproduction 6 Developing Story Ideas Ideation Beginning the Writing Process Story Sources Making an Idea Database Keeping a Journal Newspapers and Magazines Online History Legends Myths Family Stories Childhood Stories Social Science and Social History Fiction Selecting a Subject Testing a Subject Don’t Bite Off More Than You Can Chew Narrow the Frame Choosing a Central Character Character is Destiny Locating and Raising the Stakes Manipulation Dangers Using the Medium to Stir Feelings Shock Value Primary Evidence Testing for Cinematic Qualities Mood Matters Local Can be Large Subject-Driven, Character-Driven, and Plot-Driven Films Subject-Driven Films What to Avoid Displace and Transform Hands-On Learning 7 Research Developing a Proposal A Note on Film Writing Research Overview Make a Working Hypothesis Project 7-1: Developing a Brief Working Hypothesis Field Research Narrowing the Frame Taking Notes Research Methods are Subject-Driven Finding the Paradigm Shootable Evidence Making an Inventory Project 7-2: Dramatic Content Worksheet How to Film It: Style and Content Hands-On Learning 8 Developing and Pitching a Short Documentary Turning Dramatic Content into an Outline Pitching Who/What/When/Where/Why A Typical Pitch Critiquing a Pitch Expanding the Pitch to a Proposal Scheduling Signed Agreements Location Agreement Personal Release Budget Project 8-1: A Short Observational Documentary Some Short Film Proposals and Their Films Hands-On Learning 9 The Crew Developing Your Own Crew Why Crewmembers’ Temperaments Matter Small Crew Roles and Responsibilities Director Director of Photography (DP), and/or Camera Operator Sound Recordist Put Commitments in Writing Part 4: Production 10 Capturing Sound Headphones to Monitor Your Work Sound Design and Soundscapes Sound Terms
Keywords: Documentary films - Production and direction